Diagnosis and Treatment of Myocarditis - Milei, José; Ambrosio, Giuseppe (IntechOpen, 2013)
Myocarditis is a clinical syndrome, most frequently of infectious etiology, that occurs with a broad range of relatively non-specific symptoms, and consists of an inflammatory process of the heart with necrosis and degeneration of the myocardium by inflammatory infiltration of immune cells. The infection can cause direct injury of cardiomyocytes as well as immune-mediated destruction of the myocardium, leading to cardiac dysfunction. In this book, the broad aspects of myocarditis are fully presented by leading international experts. The texts are devoted to both clinical aspects and pathophysiology, and they present comprehensive reviews of the causes of myocarditis, its classification, diagnosis, and treatment, as well as myocarditis in special populations such as pediatric, peripartum and chronic chagasic myocarditis.